COLLABORATIVE TRANSFORMATION IN EFFORT TO REDUCE MATERNAL MORTALITY RATE IN PMB MESRIDA SIMARMATA, Am Keb IN MEDAN TENGGARA DISTRICT, MEDAN DENAI DISTRICT, 2023 - Simarmata, Mesrida; Astuti, Tani; Dewi, Eva Ratna; Sumita, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Introduction: SDGs are a global commitment to solving health problems. The SDGs program has a strategy to achieve targets, one of which is collaborative transformation. Many obstetric cases require cross-sectoral treatment and inter-level referrals because a health problem requires expertise and treatment that is diverse and multi-level in terms of complete facilities. A case of Mrs. N, 32 years old, came to the first level of BPM. Objective : To analyze the collaborative transformation that occurs in the treatment of thyroid gland problems. Method : Qualitative descriptive, namely analyzing a midwifery case of increased thyroid production or enlargement of the thyroid gland . This research was conducted at PMB Mesrida Simarmata, amkeb with a sample size of 1 person, namely Mrs N aged 32 years. Results with a diagnosis of hyperthyroidism were completed using a collaborative pathway between referral levels and referrals from services. As a form of collaboration in terms of funds, namely BPJS. Conclusion : With collaborative transformation , Mrs. Suggestion : It would be better to strengthen a collaborative system in terms of screening or disease prevention as well.